UM presentation / Ooi Li Ching - Ooi , Li Ching (2005)
All undergraduates of the Faculty of Computer Science and Information Technology, University of Malaya are required to do the thesis. Thesis is a compulsory subject for all of the final year students in this faculty which has divided into two phases. Each phase is supposed to complete inn each semester of final year. Thesis phase 1 (WXES3182) in the second semester. To fulfill the requirement of faculty, UM presentation has been chosen to become the title of my thesis. To success this thesis, I have implement all the knowledge and skills that I have gained throughout my 3 years study in UM to practical situations. Apart from that, I also have a chance to learn more skills of other multimedia authoring tools according to the requirements of my thesis. I believe that this will help me a lot in my future employment. UM presentation is a stand alone multimedia package that will focus more on the University of Malaya. Due to the reason where there are many people either the university students or other residents like to know more information about it. This presentation will show the user the useful information about the university especially for the first year students. Besides that, campus map will be included in this presentation to let users know how to get there and also navigate it. The system will also let users know about the facilities and services provided by UM.